Food systems actors engaged in the cocreation of agroecological innovations - Results of Year 2 engagement - Staiger-Rivas, Simone; Orjuela, Guillermo (2023)
This summary report analyzes the data from 2022, and data collected from January to October 2023 of the number and type of Food Systems Actors engaged in the cocreation of agroecological innovations. It includes seven countries, the data from Senegal missing as it is the latest country to join the Initiative. A report covering all eight countries and the entire two-year span will be published early 2024.